Multi-objective optimal scheduling of reconfigurable assembly line for cloud manufacturing. (4th May 2017) - Yuan, Minghai; Deng, Kun; Chaovalitwongse, W.A.; Cheng, Shuo
Abstract : We propose a multi-objective optimization scheduling model to improve the production efficiency of a reconfigurable assembly line. We aim to minimize the costs of assembly line reconstruction, achieve the production load equalization, and minimize the delayed workload using this model. However, the proposed multi-objective optimization model is significantly complex for conventional mathematical optimization methods. Thus, we present an efficient solution approach based on a distance sorting particle swarm optimization. Finally, a case study is conducted to illustrate the feasibility and efficiency of the proposed method. Experimental results indicate that our proposed approach can significantly improve the production efficiency (i.e. increased production load balance, minimized reconstruction cost, and minimized delayed workload).